Isolation and Identification of Plant Growth Promoting Rhizobacteria from Cucumber Rhizosphere and Their Effect on Plant Growth Promotion and Disease Suppression - Islam, Shaikhul; Akanda, Abdul M.; Prova, Ananya; Islam, Md. T.; Hossain, Md. M. (Frontiers in Microbiology, 2016)
Plant growth promoting rhizobacteria (PGPR) are the rhizosphere bacteria that may be utilized to augment plant growth and suppress plant diseases. The objectives of this study were to identify and characterize PGPR indigenous to cucumber rhizosphere in Bangladesh, and to evaluate their ability to suppress Phytophthora crown rot in cucumber. A total of sixty six isolates were isolated, out of which ten (PPB1, PPB2, PPB3, PPB4, PPB5, PPB8, PPB9, PPB10, PPB11 and PPB12) were selected based on their in vitro plant growth promoting attributes and antagonism of phytopathogens. Phylogenetic analysis of 16S rRNA sequences identified these isolates as new strains of Pseudomonas stutzeri, Bacillus subtilis, Stenotrophomonas maltophilia and B. amyloliquefaciens. The selected isolates produced high levels (26.78 to 51.28 μg mL−1) of indole-3-acetic acid, while significant acetylene reduction activities (1.79 to 4.9 µmole C2H4 mg-1 protein h-1) were observed in eight isolates. Cucumber plants grown from seeds that were treated with these PGPR strains displayed significantly higher levels of germination, seedling vigor, growth, and N content in root and shoot tissue compared to non-treated control plants. All selected isolates were able to successfully colonize the cucumber roots. Moreover, treating cucumber seeds with these isolates significantly suppressed Phytophthora crown rot caused by Phytophthora capsici, and characteristic morphological alterations in Ph. capsici hyphae that grew towards PGPR colonies were observed. Since these PGPR inoculants exhibited multiple traits beneficial to the host plants, they may be applied in the development of new, safe, and effective seed treatments as an alternative to chemical fungicides.